INOVASI PENDIDIKAN PESANTREN: MEMBANGUN GENERASI UNGGUL DAN BERDAYA SAING - Dinda Putri; Hasyim Basid; Ariana; Amiruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to explore educational innovation in Islamic boarding schools in order to build a superior and competitive generation. Using a qualitative approach and case study design, this research analyzes innovative strategies implemented in several selected Islamic boarding schools in Indonesia. Research findings show that these Islamic boarding schools have made various innovations in the curriculum by integrating the national and traditional curriculum, as well as utilizing technology in the learning process. Apart from that, developing soft skills through comprehensive training programs and adopting an active learning approach is the main focus in efforts to improve students' competency. Collaboration with various parties, including higher education institutions and the industrial sector, also expands the network and resources available to Islamic boarding schools. These innovations have a positive impact on improving the academic, religious, and social, emotional and intellectual abilities of students, so that they are able to compete in the global job market. However, this research also identified challenges faced by Islamic boarding schools, such as limited resources and resistance to change from several parties within the Islamic boarding school.